A Survey on Topology Control and Maintenance in Wireless Sensor Networks - Manish Singh (IAES Indonesian Section, 2014)
Wireless Sensor Networks (WSNs) consist of devices equipped with radio transceivers that cooperate to form and maintain a fully connected network of sensor nodes. WSNs do not have a fixed infrastructure and do not use centralized methods for organization. This flexibility enables them to be used whenever a fixed infrastructure is unfeasible or inconvenient, hence making them attractive for numerous applications ranging from military, civil, industrial or health. Because of their unique structure, and limited energy storage, computational and memory resources, many of the existing protocols and algorithms designed for wired or wireless ad hoc networks cannot be directly used in WSNs. Beside this, they offer a flexible low cost solution to the problem of event monitoring, especially in places with limited accessibility or that represent danger to humans. Applications of large scale WSNs are becoming a reality example are being a Smart Grid, Machine to Machine communication networks and smart environment. It is expected that a topology control techniques will play an important role in managing the complexity of such highly complicated and distributed systems through self-organization capabilities. WSNs are made of resource constrained wireless devices, which require energy efficient mechanisms, algorithm/protocol. Control on topology is very important for efficient utilization of networks and is composed of two mechanisms, Topology Construction (TC) and Topology Maintenance (TM). By using these mechanism various protocols/algorithm have came into existence, like: A3, A3-Coverage (A3-Cov), Simple Tree, Just Tree, etc. This paper provides a full view of the studies of above mentioned algorithms and also provides an analysis of their merits and demerits.